Design of literacy activities to promote writing with children: an experience with second graders - Ruíz C., Nubia Cecilia (Colombian Applied Linguistics Journal, 2004)
In this paper, I would like to share my experience as a kidwatcher in a private school in Bogotá, Colombia while designing and implementing a variety of literacy activities to promote writing in English in an EFL context for second grade students. It highlights the importance of understanding writing as a dynamic process as well as the role kidwatching had in helping me become a teacher who understood, respected, supported, learnt, enjoyed and loved the active manner in which children construct knowledge of the written language. At the same time, I gained insights about childrenʼs thoughts, feelings, and concerns about the world they live in. I hope, from this experience teachers are encouraged to explore their classroom contexts and make the best decisions that contribute to the development of their students as writers.